Implementing Gallery Walk Technique in Teaching Speaking to the Seventh Grade Students of SMP Darul Hikmah - Ananda Rifna Humairoh (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2022)
This study aims to solve the students’ problem in speaking session. The participants of the studyare fifteen students of the seventh grade of Darul Hikmah Junior High. By implementing gallerywalk, the students are observed upon their liveliness and initiative in speaking or presenting theirperformance during the learning process. In conclusion, this technique has been proven as thetrigger for students’ speaking ability. The researcher has got the result that during the learningprocess that was implemented by the gallery walk technique, the students have more motivationand brave to speak up in front of their friends and teachers. The objective of this study is also todescribe the implementation of modified gallery walk technique can contribute a great benefit tothe student enthusiasm in speaking English. The learners can engage and understand the topicdiscussed well and build more interaction with another learner. This study has been drawn thestudents get into the point of teaching material better by taking on this technique. The collectivedata were analyzed and observed that Gallery Walk Technique is one of potential teachingstrategies as an active-learning process